Pengembangan Aplikasi Wayang Kuis Edukatif dalam Penguatan Karakter Kebhinekaan Peserta didik SD - Raden Ayu Sekar Arum Handayani Khairunnisa; J. Julia; Diah Gusrayani (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The research conducted took the Research and Development (RnD) method using the Analyze, Design, Development, Implementation, Evaluation (ADDIE) model to develop a product. The research instruments used in obtaining data using student questionnaires, validation questionnaires for media experts, material experts, linguists, and the System Usability Scale (SUS). In addition, at the development stage to determine the feasibility of the application product developed using the ISO 9126 standard. Testing the quality of product development requires testing based on ISO 9126 standards by taking suitability, instability, adaptability, and time behavior criteria to identify the performance and quality of the products developed. Data acquisition was analyzed in a descriptive quantitative and qualitative way. The average score results obtained included a very feasible category with a score of 90.93%, the feasibility of the material content included a very feasible category with a score of 99.04%, the feasibility of the language used included a very good category with a score of 94.28%. The average score obtained from the students' response to the product developed in the individual test was 80.56%, the small group test was 99.83%, and the large group test was 93.02%. In addition, software testing has met the standards of portability characteristics on adaptability and installability indicators by obtaining 100% feasibility, as well as getting a percentage of 88.16% from the public response to the Educational Puppet Quiz application. Thus, the development of the Educational Puppet Quiz Application is feasible to use in strengthening the character of diversity of elementary school students.